Clinical application of real-time PET/CT guided targeted retroperitoneal masses biopsy in diagnosing malignant tumors - Xiaomin Li; Wanchun Zhang (BMC Cancer, 2023)
Abstract Objective To explore the feasibility, safety, and clinical application value based on the fusion image of 18 F-FDG PET/CT, for guiding retroperitoneal puncture biopsy technology and to determine the diagnosis of retroperitoneal masses in diagnosing malignant tumors. Methods From March 2019 to January 2023, 42 patients underwent 18 F-FDG PET/CT imaging and were found to have retroperitoneal lesions that required definite diagnosis; 22 were male, 20 were female, and the average age was(59.17 ± 13.23) years. According to the fused 18 F-FDG PET/CT tomographic image, the target point with the highest metabolic activity, the safest, and expected maximum sample size was selected. CT scans were acquired with the same machine and fused with 18 F-FDG PET, guiding the puncture biopsy needle to approach the expected target zone, enabling timely delivery of pathological and immunohistochemical examination of the biopsy. Success rate, total examination time, biopsy operation time, complications, CT radiation dose, pathological, and immunohistochemical results were recorded. Results All 42 patients were sampled successfully with the successful rate being 100%. The site of sampling of 42 patients accurately targeted the highest metabolic activity, the safest, and the expected maximum sample size. All 42 patients received clear diagnosis (25 cases of malignant tumors and cases of 17 benign tissues). 15 cases of patients had a change in clinical diagnosis, accounting for 35.7% of all patients, and affecting subsequent treatment plans. The average total examination time for patients was (41.3 ± 7.3) minutes, and the biopsy operation time was (29.1 ± 8.7) minutes. The effective radiation dose generated by the entire examination generated by CT guidance was (2.0 ± 0.5) mSv; no severe complications occurred in the patients. Conclusion Real-time-guided retroperitoneal puncture biopsy based on 18 F-FDG PET/CT fusion image is safe, accurate, and feasible, and can provide patients of retroperitoneal mass with clear pathological diagnosis and immunohistochemical evaluation.